Impact Of Underage Marriage On Reproductive Health In Cileles District - Ratnawati Ratnawati; Masluroh Masluroh (International Journal of Health and Pharmaceutical (IJHP), 2024)
Married women under the age of 16 are usually 10-12 times more likely to develop cervical cancer than those who are married over the age of 20. At that age the uterus of a young woman is very sensitive. The juvenile cervix is ​​more susceptible to carcinogenic stimuli because of the active process of metaplasia, which occurs in the transformation zone during the developmental period. Squamous epithelial metaplasia is usually a physiological process. But under the influence of carcinogens, cell changes can occur resulting in a pathological transformation zone (Melva, 2017). These atypical changes initiate a process called cervical intraepithelial neoplasm (CIN) which is the preinvasive phase of cervical cancer. Under the age of 18, a woman's reproductive organs are still very weak. If she is pregnant, then As a result, it will be easy to miscarry because the uterus is not that strong, making it difficult for the fetus to attach to the uterine wall. This type of research is descriptive research with the method used is a quantitative approach. The sample in this study was taken from the entire population, because the method used was total sampling with a total of 46 people. This study uses a cross-sectional or cross-sectional design which can show the relationship between the independent and dependent variables but cannot show a causal relationship. The results of the study that based on the results of the Paired Samples t Test correlation test obtained a p-value of 0.00. Because the p value is 0.00 (p <0.05), there is a significant impact of early marriage on reproductive health.